From plan to practice: development, awareness, and implementation of sports injury and illness risk management plans in a professional male football setting - Hassanmirzaei, B.; Tabben, M.; Schumacher, Y. O.; Rahali, A.; Moutaouakkil, H.; Chabbane, M.; Mokrani, M.; Ellouze, Z.; Bahr, R. (Journal of Science and Medicine in Sport, 2026)
Objectives To examine the development, stakeholder involvement, and implementation of risk management plans (RMPs) in professional football clubs in Qatar during the 2022-2023 season, with a focus on contributors to RMP creation, team awareness, and completion of mitigation tasks. Design Observational study. Method All 18 clubs that submitted an RMP were invited, and 16 participated. Data were collected during face-to-face meetings with each team's representatives using a standardized questionnaire addressing stakeholder involvement, awareness of the RMP within the team, task assignment, and implementation. A total of 324 mitigation tasks were reviewed. Implementation was rated using a six-point Likert scale. Results Sixteen professional football clubs participated in the study. Across the clubs, 331 RMP tasks were identified, of which 324 were evaluated for implementation. RMP development was primarily undertaken by team doctors, physiotherapists, and fitness coaches, with no involvement from managers or players. Implementation levels were highest when tasks were assigned to medical staff or mixed groups that included at least one medical team member. Team-related tasks had higher implementation levels than season-related tasks (p=0.024), while no meaningful association was observed between assigned risk priority and implementation levels. Conclusions In professional football clubs, the presence of medical personnel among the responsible staff was a key determinant of the higher implementation rates for mitigation tasks. Neither the risk category nor the stated priority level predicted implementation. These findings provide empirical insight into how structured risk management is operationalized in elite football and underscore the central role of medical and fitness staff in executing injury and illness prevention.